Equality measures and plans in private companies. Regulatory framework and doctrinal and judicial interpretation - Lousada Arochena, José Fernando (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2023)
The Organic Law for the effective equality of women and men of 2007 established a regulatory framework for the collective bargaining of equality measures and plans in private companies. The star measure was the obligation to implement equality plans in companies with 250 workers or more. Royal Decree-Law 6/2019 amended the regulations, among other reasons, to extend the obligation to companies with 50 workers or more. The present study is aimed at analyzing the regulatory framework currently in force, the application and interpretation that has been carried out by the courts of justice and a review of scientific doctrine.